2019
DOI: 10.22219/jtiumm.vol20.no2.182-190
|View full text |Cite
|
Sign up to set email alerts
|

A Model to Choose Hub and Route Determination

Abstract: Determining a transport hub is a strategic decision to build a good distribution flow. In this paper, We suggested a model for choosing hub locations as sources for companies. In previous studies, The determination of hub locations with a vehicle routing problem is not integrated. Therefore, This study built a model to assess the position of the hubs by considering the budget. The business should have a decision on vehicle routing with hubs to reduce total transport costs. In addition, the method of distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…For that purpose, the LRP model was developed to accommodate the determination of depot locations and vehicle routing. Another study conducted by Kevin, Aritonang, and Lesmono [23] also successfully integrated the two decision-making areas. Nagy and Salhi [24] found that location routing could decrease costs over a long planning horizon.…”
mentioning
confidence: 99%
“…For that purpose, the LRP model was developed to accommodate the determination of depot locations and vehicle routing. Another study conducted by Kevin, Aritonang, and Lesmono [23] also successfully integrated the two decision-making areas. Nagy and Salhi [24] found that location routing could decrease costs over a long planning horizon.…”
mentioning
confidence: 99%